Technology-Assisted Intervention For Children With Autism Spectrum Disorder Using Augmented Reality - Suparjoh, Suriawati; Shahbodin, Faaizah; Che Ku Mohd, Che Ku Nuraini (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
Technology-assisted intervention has potentials in improving the social, communication and behavior impairments in of children with autism spectrum disorder (ASD). Augmented reality (AR) offers multitude of possibilities and opportunities for the intervention of children with ASD. Therefore, this study identifies 13 researches from 2012 to 2018 that documented the efficacy of augmented reality applications in supporting the intervention of children with ASD. This study reviews the applications of augmented reality that nhanced the intervention for children with autism in (i) social skills, (ii) communication skills, and (iii) behavior skills. The conclusion reports the significant roles of augmented reality as technology-assisted intervention for children with ASD.